Engineering a switchable single‐chain TEV protease to control protein maturation in living neurons - Pietro Renna; Cristian Ripoli; Onur Dagliyan; Francesco Pastore; Marco Rinaudo; Agnese Re; Fabiola Paciello; Claudio Grassi (Wiley, 2022)
Abstract Engineered proteases are promising tools to address physiological and pathophysiological questions as well as to develop new therapeutic approaches. Here we introduce a new genetically encoded engineered single‐chain tobacco etch virus protease, allowing to control proprotein cleavage in different compartments of living mammalian cells. We demonstrated a set of controllable proteolytic effects, including cytosolic protein cleavage, inducible gene expression, and maturation of brain‐derived neurotrophic factor (BDNF) in the secretory pathway thus showing the versatility of this technique. Of note, the secretory pathway exhibits different characteristics from the cytosol and it is difficult to target because inaccessible to some small molecules. We were able to induce ligand‐mediated BDNF maturation and monitor its effects on dendritic spines in hippocampal pyramidal cells and in the mouse brain. This strategy paves the way to dissect proteolytic cleavage product signaling in various processes as well as for future therapeutic applications.